THE ROLE OF PANCASILA IN NATIONAL INTEGRATION: STRATEGIES FOR ADDRESSING SOCIAL CHALLENGES AND DIVERSITY IN INDONESIA - Bambang Yuniarto; Tari Sriningsih; Prita Oktavia; Azra Syeren Fadila; Anita Sari; Faiha Az-Zahra Khan (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This research aims to analyze the role of Pancasila in maintaining national integration in Indonesia, as well as to identify social challenges that potentially threaten national unity. The main issues include the persistence of intolerance, social inequality, and the negative influences of globalization and digital media which weaken the value of unity. These issues demand an in-depth review of the effectiveness of Pancasila as a filter and unifying agent in this disruptive era. The research method employs a qualitative approach with literature study as the primary data source. The analysis was conducted by examining literature on the implementation of Pancasila's values in societal life and educational practices in Indonesia. The analytical focus was placed on identifying the mechanisms that make the principles of Pancasila relevant in responding to horizontal conflicts. The results indicate that Pancasila plays a crucial role as an ideological foundation capable of uniting diversity through its core values. Pancasila serves as a guideline in building national character and directing public policies to be oriented towards the interests of all people. Strengthening the internalization of Pancasila's values through character education and inclusive policies is the main strategy for preventing national disintegration. Therefore, systematic and continuous efforts are needed to implement the values of Pancasila by emphasizing cross-cultural dialogue and the enforcement of just laws, so that national integration can be maintained amidst the challenges of the modern era. This study recommends the reactivation of national forums as a means to consolidate the values of the state's foundation.